Effects of Banana Compost on Growth, Development and Productivity of Sorghum bicolor Cultivar (Tabat) - Saeed, Badreldin Ahmed; ElNour, Mawahib E M; G, Elfadil A (JOURNAL OF ADVANCES IN BIOLOGY, 2015)
The research was targeted to determine the effect of organic fertilizer prepared from the composting of banana waste on growth, development, morphologically and productivity of Sorghum bicolor (Tabat). In order to convert huge of banana residues parts wastes and to reduce the chemicals fertilizers pollution, the banana compost was used on Sorghum bicolor in this study. This type of organic fertilizer detected magnitude of morphological changes on different parts of the plant used in this experiments. The other uses of thebanana compost were the improvement of texture, structure, water holding capacity, permeability and productivity ofthe soil. The experiments were conducted at the green house of the Department of Biological and Biotechnology and Environmental Science, Al Neelain University, Khartoum, Sudan. In these experiments banana compost was used at different levels (10g , 20g and 30g) for each 500g of clay soil, which were equivalents to 1 ton, 2 tons and 3 tons per fedan respectively. Two controls, control virgin soil and control with recommended nitrogen level were used. The results showed that the treatments with 3 tons banana compost level had its significant ( P < 0.05) over the both controls with a maximum growth rate in the plants morphology as well as length of the plants of 11.9cm. and the mass productivity of one gram.